2019
DOI: 10.2147/ndt.s194264
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of achieving remission in schizophrenia patients treated with paliperidone palmitate 3-month formulation</p>

Abstract: PurposeLong-acting injectable (LAI) antipsychotic paliperidone palmitate 3-month formulation (PP3M) is indicated in the United States for the treatment of schizophrenia only after adequate treatment with paliperidone palmitate 1-month formulation (PP1M) for ≥4 months. This analysis aimed to identify patient and disease characteristics during PP1M treatment associated with greater likelihood of achieving remission after transition to PP3M.MethodsA post hoc analysis of a randomized, Phase III, double-blind, noni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Another research [ 25 ] identified patient and disease characteristics during PP1M treatment associated with greater likelihood of achieving remission after transition to PP3M. Patients with early clinically meaningful improvements in disease symptoms and severity while establishing stable PP1M dosage were more likely to achieve remission after transition to PP3M.…”
Section: Discussionmentioning
confidence: 99%
“…Another research [ 25 ] identified patient and disease characteristics during PP1M treatment associated with greater likelihood of achieving remission after transition to PP3M. Patients with early clinically meaningful improvements in disease symptoms and severity while establishing stable PP1M dosage were more likely to achieve remission after transition to PP3M.…”
Section: Discussionmentioning
confidence: 99%
“…Given that they were switched to the same drug, we can assume that the reason for the switch was not related to paliperidone itself, but rather the formulation and the frequency of its use. In conventional trials, PP1M and PP3M have near identical efficacy and tolerability [18].…”
Section: Reasons For Discontinuationmentioning
confidence: 98%
“…The Clinical Anti-psychotic Trials of Intervention Effectiveness (CATIE) study reported that over 70% of patients discontinued oral medications within 1.5 years as a result of medication-related factors such as adverse events and lack of perceived efficacy [ 32 ]. Importantly, non-adherence contributes to disease relapse [ 1 , 7 , 32 ], higher rates of psychiatric rehospitalization [ 2 , 10 , 33 , 34 ], and increased need for ER visits [ 33 , 34 ]. The high treatment completion rate in our study suggests good adherence, which may have translated to the high symptomatic remission rate (71%) and low hospitalization (1%) and ER visit rates (3%) after 12 months of PP3M treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic remission is an important milestone in the management of schizophrenia [ 1 ]. Without adequate symptom control, patients continue to suffer from disruptions in lifestyle, productivity and an increased risk of hospitalization [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation